The evaluation of color and color difference according to the layering placement of Incisal shade composites on the body composites of the indirect resin restoration - Su-Jung Park; Han-Young Lee; Myong-Yun Nah; Hoon-Sang Chang; Yun-Chan Hwang; Won-Mann Oh; In-Nam Hwang (Korean Academy of Conservative Dentistry, 2011)
Objectives The aim of this study was to evaluate the surface color of indirect resin restoration according to the layering placement of different shade of incisal composite. Materials and Methods In this study, CIE L*a*b* value of 16 Body composite of Tescera ATL (Bisco, Schaumburg IL,USA) was measured by spectrophotometer (NF999, Nippon Denshuku, Japan), and compared to CIE L*a*b* value of Vitapan shade guide. Nine shade Incisal composite of Tescera ATL were build-up to 1 mm thickness on Body composites inlay block, and CIE L*a*b* value was measured. Incisal composite was ground to 0.5 mm thickness and CIE L*a*b* value was re-measured. Color difference between Body composite and Incisal composites layered on Body composite was calculated as a function of thickness. Results Color difference between corresponding shade of Tescera Body composite and Vitapan shade guide was from 6.88 to 12.80. L* and b*value was decreased as layering thickness of Incisal composite on Body composite was increased. But, a* value did not show specific change tendency. Conclusions Surface color difference between Body composites and Incisal composites layered on Body composite was increased as the layering thickness of Incisal composite increased (p < 0.05).